Development status and enlightenment of aviation medical rescue (航空医疗救援发展现状及启示) - LI Haishui (李海水); WANG Jingjing (王静静); SHEN Yanling (申艳玲); WANG Shupeng (王书鹏); DUAN Jun (段军) (中西医结合护理)
Aviation medical rescue has the advantage of quick response and safe in emergency rescue and enters a stage of rapid growth. Given a late start of Aviation medical rescue in China, its shortcoming lies in dispatch system, equipment allocation, management system and personnel training. These papers summarized the development status of aviation medical rescue, and provided suggestions for the development of Aviation medical rescue business in China. (航空医疗救援具有迅速安全的优势, 目前在国内处于快速发展阶段, 由于起步较晚, 目前仍面临调度体制不完善、设备配给不足、管理制度欠缺、人员培训不规范等问题。本文主要综述了国内外航空医疗救援的发展现状, 并提出相关建议, 以期进一步促进国内航空医疗救援事业的发展。)